Synthesis and characterization of TAPO-31 molecular sieves using tripropylamine template - Venkatathri, N.; Shetty, V. N. (Catalysis Communications, 2006)
TAPO-31 was synthesized hydrothermally using a novel template tri-n-propylamine for the first time. C and N analysis shows the butanol from titanium tetrabutoxide plays an important role in the synthesis. The incorporation of titanium into framework of phosphorous and both aluminiurn and phosphorous sites was suggested from elemental analysis. Isomorphous substitution of titanium (III) in AlPO framework was confirmed from ESR and (31)p MASNMR spectra. UV-Vis and XPS spectra revealed a partial oxidation of framework titanium (III) into titanium (IV) in the calcined TAPO-31 and thus the presence of redox centers in the products. The higher titanium content (Al/Ti = 10) TAPO-31 sample shows higher activity for phenol hydroxylation compared to lower titanium content (Al/Ti = 20) and Titanium impregnated AIPO(4)-31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ESR; FT-IR; MASNMR; SEM; TAPO-31; TG/DTA; tripropylamine; UV-Vis; XPS; XRD